Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.248
|View full text |Cite
|
Sign up to set email alerts
|

The Style of Tetris is€Possibly Tetris?: Creative Professionals Description of Video Game Visual Styles

Abstract: Despite the increasing importance of video games in both cultural and commercial aspects, typically they can only be accessed and browsed through limited metadata such as platform or genre. We explore visual styles of games as a complementary approach for providing access to games. In particular, we aimed to test and evaluate the existing visual style taxonomy developed in prior research with video game professionals and creatives. User data were collected from video game art and design students at the DigiPen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They have studied how humans interact as they play Tetris and how this relates to primate socialization in general, observing that "baboon social intelligence contrasts both with that of Tetris players and human infants, because both have the ability to provoke epistemic effects" [27]. Other human angles have been studied as well, including studying styles of play [18,55], humanity's suboptimal choices [80], eye movement while playing [51,61,62,85], and how champion Tetris players play, including the relationship between Hick's Law and…”
Section: Related Workmentioning
confidence: 99%
“…They have studied how humans interact as they play Tetris and how this relates to primate socialization in general, observing that "baboon social intelligence contrasts both with that of Tetris players and human infants, because both have the ability to provoke epistemic effects" [27]. Other human angles have been studied as well, including studying styles of play [18,55], humanity's suboptimal choices [80], eye movement while playing [51,61,62,85], and how champion Tetris players play, including the relationship between Hick's Law and…”
Section: Related Workmentioning
confidence: 99%
“…Digital games have evolved in accordance with advanced computer technology and have affected visual styles by making them more diverse and complex (Keating et al, 2017). Discussion on visual styles in academia and online community forums has indicated an increasing interest in exploring artistic elements and aesthetic appeal.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, Rossi et al (2014) introduced the mood domain visual aesthetics, such as brightness, darkness, colour, and black and white. Keating et al (2017) broadened the mood domain visual style classification into achromatic, monochromatic, and colourful. Recently, Cho et al (2018) suggested that bright, dark, colourful, and black and white visual style classifications are agreeable amongst game players for the mood domain.…”
Section: Figurementioning
confidence: 99%
“…While blue and green evoke relaxing feelings, green also creates comfort (Kaya and Epps, 2004;Kennedy, 2014;Roohi and Forouzandeh, 2019). However, independent of color shade, bright or pastel colors are associated with childlike appeal and thus induce joy (Marcus, 2015;Keating et al, 2017). Adventure games such as King's Quest I: Quest for the Crown (Sierra Entertainment, 1983) and Arise: A Simple Story (Piccolo Studio S.L., 2019) make great use of bright colors to generate charming environments (Karhulahti, 2011;Edge, 2020).…”
Section: Colors and Texturesmentioning
confidence: 99%